Educational Concepts Based on Boarding Schools Curriculum To Achieve a Competitive Advantage - Hasan, M. Fuad; Sanjaya, Elok; Winarko, Rudy (Prosiding Seminar, 2023)
The research is motivated by society's view that Islamic boarding school curriculum education is still traditional, so graduates cannot compete adequately. This study aims to analyze and describe: a). educational innovation at SMP Islam Plus Hidayatut Thullab; b). the concept of Islamic boarding school curriculum-based education; c). competitive advantage in education. The research was conducted using a descriptive method with a qualitative approach utilizing in-depth interviews to obtain information. The data obtained is analyzed descriptively and interpretatively through data reduction, presentation, and conclusion. The research results will be drawn conclusions using the triangulation technique by presenting data in the form of research results that have been carried out, namely: a). Educational innovation is carried out in the form of a pesantren education curriculum; b). the application of the pesantren curriculum is carried out without eliminating the concept of national education; c). Academic student graduation is achievements in the form of science, noble character and intelligence in religion evidence competitive advantage